PENGARUH TINGKAT SUKU BUNGA DAN KUALITAS LAYANAN TERHADAP PENYALURAN KREDIT PADA PT BPR NUSUMMA JATIM CABANG JOMBANG - Lailatus Sa’adah; Rahmawati, Ita; ., Yunaidah (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2022)
The variety of interest rates offered allows customers to choose to take banking credit then the good quality of service by the bank will give customers consideration in taking credit. The objectives of the study are (1) To find out and explain the effect of interest rates on lending, (2) To find out and explain the effect of service quality on lending, (3) To determine the effect of interest rates and service quality together on lending. The approach of this research is to use quantitative methods. The sample taken was 109 customers of PT BPR Nusumma Jatim Jombang Branch. The results showed that (1) There is no effect of interest rates on lending, (2) There is an influence of service quality on lending, (3) There is an influence of interest rates and service quality on lending.